Impact of Ambiversion on Collaboration Among Diverse Groups - Moses Adeleke Adeoye; Kamoru Abidoye Tiamiyu; Musa Aremu Mahmud; Hassanat Abdullateef Jimoh (Jurnal Pedagogi dan Pembelajaran, 2023)
The coexistence of extroverted and introverted tendencies characterizes the psychological trait known as ambiversion. The impact of ambiversion on collaboration among various groups has received limited attention in the literature. This study examines the relationship between ambiversion and collaboration among individuals with culturally diverse backgrounds, using three leading theoretical models in personality psychology: the HEXACO Model, the Big Five Model, and the Myers-Briggs Type Indicator Model (MBTI). This type of research is qualitative research (literary study). The data collected and analyzed are secondary data from research results such as relevant books, journals, articles, internet sites, and others. Data analysis techniques in this study used content analysis data analysis techniques. The results of the study, namely, in particular the HEXACO Model, highlight the importance of openness to experience in facilitating collaboration among various groups. In contrast, the Big Five Model emphasizes the role of conscientiousness in this relationship. The MBTI model must provide significant evidence of its contribution to the relationship between ambiversion and collaboration between diverse groups. It concluded that individuals and organizations could create ways to encourage successful collaboration and teamwork while leveraging the capabilities of various team members by identifying the strengths and specific problems of ambiverts.